The Clinical Study about Honilirls Placenta Herbal Acupuncture on Bell's Palsy - Lee Chae-Woo; Kim Hong-gi; Heo Sung-woong; Jung Kyoung-kun; Ahn Chang-Beohm; Song Choon-Ho; Jang Kyung-Jeon; Kim Cheol-Hong; Youn Hyoun-Min (Korean Pharmacopuncture Institute, 2005)
Objectives : This study has been designed and performed to identify the effect on Bell's palsy according to the injection of herbal medicine induced from the Hominis Placenta. Methods : We measured the facial palsy changes of the patients who were admitted for Bell's palsy in the Oriental Medical hospital of Dongeui medical center from 03-01-2004 to 07-31-2004. Bell's palsy patients were divided into two groups. One group(A group) was injected with Hominis Placenta herbal acupuncture. The other group(B group) was injected with normal saline. Then effects of these treatment was evaluated by Yanagihara's unweighted grading system. Results : A group was marked more higher than B group in treatment outcome. we discovered that it is significant differences between two groups after 4 week. Conclusions : These results provided that A group is more effective than B group. For clearly proving the effect of Hominis Placenta herbal acupuncture on Bell's palsy, it is need more sample's number and more treatment's duration.